Impact of floods on protected areas of CBR - Архіпова, Г.І.; Ярова, С.М. (Proceedings of National Aviation University (archive), 2009)
Natural and technogenic factors which are considered influence on flooding in reserved territory of Karpatsky biospheric reserve.